EFFORTS TO HANDLE INTERNATIONAL DISPUTES THROUGH SUBJECTS INTERNATIONAL LAW - Putu Darmika (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2023)
This article aims to (1) find out clearly what is meant by international law, (2) find out how the development of international law, and (3) to know what kinds of subjects of international law in dispute resolution itself. The data collection technique used is by quoting from several book sources as well as from journals and papers that have been read before. The results of the discussion of this journal show that (1) International Law is a positive law. Where the purpose of the law itself is to create and realize justice in international. (2) The development of international law is important because in essence as a law that introduces the concept of an archipelagic state, a means of intervention to a means of suppressing developing countries, which of course in this development for the Indonesian people to strengthen cooperation in the fields of economy, politics, security, and education. (3) There are several ways to resolve disputes under international law, namely, through peaceful settlement of disputes contained in the United Nations Charter, namely Article 2 paragraph (3) of The Charter of the United Nations (UN Charter). And it can also be done in terms of kinship or peace, namely negotiation, investigation, mediation, conciliation and arbitration.